Synergistic effects of black ginseng and aged garlic extracts for the amelioration of nonalcoholic fatty liver disease (NAFLD) in mice. Issue 6 (4th May 2021) - Jiang, Guihun; Ramachandraiah, Karna; Murtaza, Mian Anjum; Wang, Lili; Li, Shanji; Ameer, Kashif
Abstract: Nonalcoholic fatty liver disease (NAFLD) is a chronic liver disease that can lead to carcinoma, cirrhosis, and death. Since no approved medications are available, dietary interventions that include bioactive compounds have been recommended. This study investigated the effects of black ginseng extracts (BGE) and aged black garlic extracts (AGE) on high‐fat diet (HFD)‐induced obese mice. Micrograph of liver tissues of mice fed with BGE and AGE showed less lipid droplets. The BGE and AGE supplements individually and in combination lowered the marker enzymes, aminotransferase (AST), and alanine aminotransferase (ALT) levels indicating their hepatoprotective effects. Compared to the plants extracts alone, the combination of the extracts resulted in lower total cholesterol (TC) and low‐density lipoproteins cholesterol (LDL‐C), which are risk markers for cardiovascular morbidity and mortality. Diets with the combination of BGE and AGE supplements had higher superoxide dismutase (SOD), glutathione peroxidase (GSH‐Px) activities, and lower malondialdehyde indicating the synergistic effects of the extracts. Irrespective of the diet type, all treated groups showed lower tumor necrosis factor (TNF‐α) values as compared to HFD, which indicated overall immunomodulatory effect of both extracts. Therefore, the innovative formulation formed by the combination of BGE and AGE can provide hepatoprotective effects via modulating glycometabolism, lipometabolism, oxidative stress, and inflammation in mice. Abstract : The innovative formulation formed by the combination of BGE and AGE can provide hepatoprotective effects via modulating glycometabolism, lipometabolism, oxidative stress, and inflammation in mice.